Thermal barrier coating bonding layer with oxidation resistance, mutual diffusion resistance, high toughness and plasticity and preparation method of thermal barrier coating bonding layer

By doping Y, Hf and Fe elements into the Ni3Al bonding layer and preparing the Ni3Al (YHfFe) bonding layer by using cathode arc ion plating technology, the problem of insufficient element interdiffusion and oxidation resistance during high-temperature service in the prior art is solved, and high toughness and excellent oxidation resistance are achieved.

CN119800284APending Publication Date: 2025-04-11XIDIAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023869.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the high-temperature service, the existing thermal barrier coating bonding layer causes phase transition and brittle topological tight phase precipitation due to elemental interdiffusion, which affects the mechanical properties of the high-temperature alloy matrix and lacks oxidation resistance, which easily leads to excessive growth of the oxide film and peeling of the outer ceramic layer.

Method used

Y, Hf and Fe elements are simultaneously doped in the Ni3Al bonding layer, and the Ni3Al (YHfFe) bonding layer is prepared by cathode arc ion plating process, and annealed heat treatment is performed in a high-temperature vacuum environment to enhance the oxidation resistance and tough plasticity of the coating.

Benefits of technology

It improves the oxidation resistance and tough plasticity of the Ni3Al bonding layer, reduces oxidative weight gain and elemental interdiffusion, avoids brittle fracture of the bonding layer during service, and has excellent service performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800284A_ABST
    Figure CN119800284A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-oxidation anti-interdiffusion high-toughness plastic thermal barrier coating bonding layer and a preparation method thereof, and the bonding layer comprises the following elements by atomic percent: 0.1 to 1 weight percent of Y, 0.1 to 1 weight percent of Hf, 0.1 to 2 weight percent of Fe, 12 to 14 weight percent of Al and 83 to 87 weight percent of Ni. The method comprises the following steps: carrying out ion etching on the surface of a pretreated high-temperature alloy substrate; plating a Y, Hf and Fe doped Ni3Al coating on the surface of the high-temperature alloy substrate subjected to ion etching by adopting a cathode arc ion plating process to obtain a Ni3Al (YHfFe) bonding layer; carrying out annealing heat treatment on the Ni3Al (YHfFe) bonding layer in a high-temperature vacuum environment; according to the Ni3Al (YHfFe) bonding layer prepared through the method, the twin boundary density is increased, the grain size and hardness are reduced, the oxidation weight increment is reduced, meanwhile, the oxidation resistance, toughness and plasticity of the Ni3Al bonding layer are improved, brittle fracture of the bonding layer in the service process is avoided, and excellent service performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal barrier coatings for turbine blades, and in particular relates to an oxidation-resistant, interdiffusion-resistant, high-toughness and plasticity thermal barrier coating bonding layer and a preparation method thereof. Background Art

[0002] Turbine blades are widely used in aero engines, marine engines, gas turbines and other fields. Since the temperature that turbine blades are subjected to during operation is higher than the melting point of the nickel-based alloy material used in turbine blades, reducing the blade temperature or improving the temperature bearing capacity of the blade has become a key issue that needs to be urgently solved. At present, the industry and academia mainly increase the service temperature of turbine blades by spraying thermal barrier coatings with thermal protection on the surface of turbine blades. Existing thermal barrier coatings are usually composed of an outer ceramic layer and an inner metal bonding layer, but the existing bonding layer system is mostly based on β-NiAl phase, which has a high Al content. During high-temperature service, elements will diffuse with the single crystal high-temperature alloy matrix. This element interdiffusion will cause phase transformation in the high-temperature alloy substrate of the turbine blade and the precipitation of brittle topological dense phases, which seriously affects the mechanical properties of the single crystal high-temperature alloy matrix, such as high-temperature fatigue performance and creep performance, and ultimately leads to blade failure. Therefore, it is urgent to develop new thermal barrier coating bonding layer materials.

[0003] Among the many candidate materials for bonding layers, Ni3Al has attracted widespread attention because of its "phase equilibrium" characteristics with the substrate, which can effectively slow down the mutual diffusion of elements with the substrate. In addition, the concentration of Al elements in Ni3Al is higher than that in the γ / γ' dual-phase bonding layer, so its oxidation resistance is better than that of the γ / γ' dual-phase bonding layer. At present, Ni3Al has excellent high-temperature strength, high hardness, oxidation resistance and creep resistance, and matches the thermal expansion coefficient of commonly used substrate materials. However, Ni3Al material has two significant defects when used as a bonding layer for thermal barrier coatings. One is insufficient oxidation resistance and the other is intrinsic brittleness.

[0004] Since the Al content in Ni3Al is lower than that of β-NiAl phase, a densely structured alumina phase will be generated in the early stage of high-temperature oxidation, which provides protection to a certain extent. However, as the oxidation proceeds, the Al element is not fully provided, so that the Al concentration is reduced to below the critical concentration that can generate stable alumina, and finally non-protective spinel and nickel oxide phases are generated. The growth rate of these phases is very fast, resulting in excessive growth of the oxide film, which may eventually cause the outer ceramic layer to peel off. Another significant defect of Ni3Al is its intrinsic brittleness, especially its extremely poor plasticity at room temperature and medium and low temperatures. It is easy to undergo brittle fracture when subjected to external stress or thermal cycling, resulting in coating failure.

[0005] In view of the poor oxidation resistance of Ni3Al coating, the most commonly used solution is to dope active elements with higher oxygen affinity in the coating. For example, in the literature (Yao H, Yang L, Bao Z, et al. Low inter-diffusivity γ'-base bondcoats for single crystal superalloy René N5.I: Primary study of microstructures and oxidation behaviors at 1100℃[J]. Corrosion Science, 2019, 147: 299-312.), Cr, Co, Re, Ta, Hf, Y and other elements are added to the Ni3Al coating on the single crystal superalloy substrate. However, there are too many doped elements in the coating system in this scheme. On the one hand, elements such as Co, Re, and Ta are expensive, which will increase the cost of the coating. Secondly, these elements will generate brittle topological dense phases inside the coating, reducing the plasticity and toughness of the coating.

[0006] Other researchers have also proposed to dope different elements to improve the mechanical properties of Ni3Al materials, but the effect is not obvious. Dimiduk DM et al. (Dimiduk DM, Weddington VL, Lipsitt HA. Effects of Fe and Mn Additions on the Ductility and Fracture of Ni3Al [J]. MRS Online Proceedings Library, 1986, 81: 221-228.) doped Mn alloy elements in Ni3Al intermetallic compounds, and Raju SV et al. (Raju SV, OniAA, Godwal BK, et al. Effect of B and Cr on elastic strength and crystal structure of Ni3Al alloys under high pressure [J]. Journal of Alloys andCompounds, 2015, 619: 616-620.) Although doping B alloying elements into Ni3Al intermetallic compounds can enhance the bonding strength of grain boundaries through solid solution strengthening and reduce the risk of grain boundary embrittlement, its grain refinement effect is not obvious, and the doping amount needs to be strictly controlled. If the doping amount is too much, it may lead to increased brittleness of the alloy, especially at high temperatures, it may not provide sufficient ductility.

[0007] Therefore, the existing technology cannot simultaneously improve the oxidation resistance and toughness and plasticity of the Ni3Al bonding layer. Summary of the invention

[0008] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an oxidation-resistant, anti-interdiffusion, highly tough and plastic thermal barrier coating bonding layer and a preparation method thereof. By simultaneously doping Y, Hf and Fe elements in the Ni3Al bonding layer, the twin boundary density of the prepared Ni3Al (YHfFe) bonding layer is increased, the grain size and hardness are reduced, and the oxidation weight gain is reduced. At the same time, the oxidation resistance and toughness and plasticity of the Ni3Al bonding layer are improved, the brittle fracture of the bonding layer during service is avoided, and the bonding layer has excellent service performance.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] An oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer, wherein the element composition of the bonding layer comprises, by atomic percentage, 0.1-1wt.% Y, 0.1-1wt.% Hf, 0.1-2wt.% Fe, 12-14wt.% Al, and 83-87wt.% Ni.

[0011] The element composition of the bonding layer includes, by atomic percentage, 1 wt.% Y, 1 wt.% Hf, 2 wt.% Fe, 13 wt.% Al, and 83 wt.% Ni.

[0012] A method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer comprises the following steps:

[0013] Step 1: performing ion etching on the pretreated surface of the high-temperature alloy substrate;

[0014] Step 2: using a cathode arc ion plating process to plate a Ni3Al coating doped with Y, Hf, and Fe on the surface of the high-temperature alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer;

[0015] Step 3: Perform annealing heat treatment on the Ni3Al(YHfFe) bonding layer obtained in step 3 in a high temperature vacuum environment.

[0016] In step 1, the high-temperature alloy substrate is a high-temperature nickel-based alloy substrate, and the pretreatment operation is: grinding and polishing and cleaning the surface of the high-temperature nickel-based alloy substrate in sequence, so that the surface of the high-temperature nickel-based alloy substrate is mirror-like and smooth.

[0017] The conditions for ion etching in step 1 are: current of 80-120A, argon gas is filled into the vacuum chamber, bias voltage is 300-600V, gas flow rate is 100-250sccm, temperature is 300-400°C, and etching time is 10-30min.

[0018] The target material used to prepare the bonding layer in step 2 is Ni3Al (YHfFe) target material.

[0019] The parameters of the arc ion plating in step 2 are: current of 80-150A, argon gas is filled into the vacuum chamber, the gas pressure is 1-2Pa, the gas flow rate is 100-250sccm, the temperature is 300-400°C, and the spraying time is 100-400min.

[0020] In step 3, the annealing temperature is 900-1100° C. and the time is 2-6 hours.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. Compared with the traditional β-NiAl phase bonding layer, the present invention designs a γ'-Ni3Al phase bonding layer, which has a "phase equilibrium" relationship with the substrate and has a low Al content (12-14wt.%), which can inhibit the mutual diffusion of elements between the bonding layer and the substrate, thereby solving the technical problem of mutual diffusion of elements between the bonding layer system and the blade high-temperature alloy substrate in the prior art.

[0023] 2. The present invention can improve the oxidation resistance of the bonding layer by doping two active elements, Y and Hf, into the Ni3Al bonding layer, thereby compensating for the technical problem of poor oxidation resistance of the bonding layer caused by low Al content.

[0024] 3. Compared with the existing Mn and B element doping, the present invention dopes Fe element into the Ni3Al bonding layer so that the Fe element is more evenly distributed in the alloy matrix, avoiding stress concentration at the multiphase interface. Fe element doping can refine the grains and homogenize the organizational structure. Finer grains help to prevent the expansion of cracks and reduce the generation of crack sources. This structural improvement can significantly improve the toughness of the alloy and increase the crack resistance of the alloy at high temperatures, thereby providing Ni3Al alloy with better toughness performance; and Ni3Al-based alloys can form a stable γ' phase (L12 structure). This phase structure has good thermal stability at high temperatures, so that the Fe-doped alloy has better durability in high-temperature applications such as aerospace.

[0025] 4. The present invention adopts the method of cathode arc ion plating to prepare the Ni3Al (YHfFe) bonding layer. Since the cathode arc ion plating process has good plating properties, the bonding layer can be deposited on the surface of blades with irregular shapes, and the preparation method has low cost and high efficiency.

[0026] In summary, the present invention simultaneously dopes Y, Hf and Fe elements into the Ni3Al bonding layer to obtain a Ni3Al (YHfFe) bonding layer with increased twin boundary density, reduced grain size and hardness, and reduced oxidation weight gain, while improving the oxidation resistance and toughness and plasticity of the Ni3Al bonding layer, avoiding brittle fracture of the bonding layer during service, and having excellent service performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A flow chart of a method for preparing an oxidation-resistant, anti-interdiffusion, high-toughness, and plastic thermal barrier coating bonding layer provided in an embodiment of the present invention.

[0028] Figure 2 This is a grain distribution diagram of the Y-, Hf- and Fe-doped Ni3Al coating prepared in Example 1 provided by the present invention.

[0029] Figure 3 This is a grain distribution diagram of the Y-, Hf- and Fe-doped Ni3Al coating prepared in Example 2 provided by the present invention.

[0030] Figure 4 This is a grain distribution diagram of the Y-, Hf- and Fe-doped Ni3Al coating prepared in Example 3 provided by the present invention.

[0031] Figure 5 This is a grain distribution diagram of the Y-, Hf- and Fe-doped Ni3Al coating prepared in Example 4 provided by the present invention.

[0032] Figure 6 This is a grain distribution diagram of the Y-, Hf- and Fe-doped Ni3Al coating prepared in Example 5 provided by the present invention.

[0033] Figure 7 This is a grain distribution diagram of the pure Ni3Al coating prepared in Comparative Example 1 provided by the present invention.

[0034] Figure 8 XRD diagrams of the Y-, Hf- and Fe-doped Ni3Al coatings prepared in Example 5 and Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0036] An anti-oxidation and anti-interdiffusion high-toughness plastic thermal barrier coating bonding layer, the element composition of the bonding layer includes: in atomic percentage, 0.1-1wt.% Y, 0.1-1wt.% Hf, 0.1-2wt.% Fe, 12-14wt.% Al, 83-87wt.% Ni; the bonding layer is a single-phase γ'-Ni3Al, such as Figure 8 shown.

[0037] like Figure 1 As shown, a method for preparing an oxidation-resistant, anti-interdiffusion, high-toughness, and plastic thermal barrier coating bonding layer specifically comprises the following steps:

[0038] Step 1: pre-treating the surface of the high-temperature alloy substrate;

[0039] The high-temperature alloy substrate is a high-temperature nickel-based alloy substrate, and the surface of the high-temperature nickel-based alloy substrate is polished and cleaned in sequence, so that the surface of the high-temperature nickel-based alloy substrate is mirror-like and smooth;

[0040] The surface of the high-temperature nickel-based alloy substrate was polished with 80#, 240#, 400#, 600#, 800#, 1000#, 1500# and 2000# sandpaper in turn, and then the sample surface was polished into a mirror surface with 1μm diamond polishing liquid and 0.06μm silicon oxide polishing liquid in turn, and ultrasonically cleaned in anhydrous ethanol for 15 minutes, so that the surface of the high-temperature nickel-based alloy substrate was mirror-like and smooth;

[0041] Step 2: ion etching the surface of the pretreated high-temperature alloy substrate to remove residual impurities on the surface and eliminate residual stress on the surface; the conditions for ion etching are: current of 80-120A, argon gas filled in the vacuum chamber, bias voltage of 300-600V, gas flow rate of 100-250sccm, temperature of 300-400°C, and etching time of 10-30min;

[0042] Step 3: using a cathode arc ion plating process to plate a Ni3Al coating doped with Y, Hf, and Fe on the surface of the high-temperature alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer; the target material used to prepare the bonding layer is a Ni3Al (YHfFe) target material; the parameters of the arc ion plating are: current of 80-150A, argon gas is filled in the vacuum chamber, the gas pressure is 1-2Pa, the gas flow rate is 100-250sccm, the temperature is 300-400°C, and the spraying time is 100-400min;

[0043] The preparation process of the Ni3Al (YHfFe) target is as follows:

[0044] Using nickel powder, aluminum powder, yttrium powder, hafnium powder and iron powder with a purity of 99.99%, weighing and mixing according to the atomic percentage of each element in the actual bonding layer to be prepared, vacuum melting is performed three times to obtain an alloy ingot, which is further machined according to the actual target size required by the multi-arc ion plating machine;

[0045] Step 4: Use a high-temperature vacuum heat treatment furnace to perform annealing heat treatment on the Ni3Al(YHfFe) bonding layer obtained in step 3 in a high-temperature vacuum environment to enhance the crystallinity of the coating crystals and promote uniform distribution of elements; the annealing temperature is 900-1100°C and the time is 2-6h.

[0046] Example 1

[0047] An oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer, wherein the element composition of the bonding layer comprises, by atomic percentage, 0.1 wt.% of Y, 0.3 wt.% of Hf, 0.1 wt.% of Fe, 13.22 wt.% of Al, and 86.28 wt.% of Ni.

[0048] A method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer specifically comprises the following steps:

[0049] Step 1: pretreating the surface of the high-temperature nickel-based alloy substrate;

[0050] The surface of the high-temperature nickel-based alloy substrate is polished and cleaned in sequence, so that the surface of the high-temperature nickel-based alloy substrate is mirror-like and smooth;

[0051] Step 2: ion etching the surface of the pretreated high-temperature nickel-based alloy substrate to remove residual impurities on the surface and eliminate residual stress on the surface; the conditions of ion etching are: current of 100A, argon gas filled in the vacuum chamber, bias voltage of 400V, gas flow rate of 180sccm, temperature of 350°C, and etching time of 20min;

[0052] Step 3: a Ni3Al coating doped with Y, Hf, and Fe is plated on the surface of the high-temperature nickel-based alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer; the target material used to prepare the bonding layer is a Ni3Al (YHfFe) target material; the parameters of arc ion plating are: current of 110A, argon gas is filled in the vacuum chamber, the gas pressure is 1.5Pa, the gas flow rate is 180sccm, the temperature is 350°C, and the spraying time is 240min;

[0053] Step 4: The Ni3Al(YHfFe) bonding layer obtained in step 3 is annealed at 1050°C for 4 hours in a high-temperature vacuum environment using a high-temperature vacuum heat treatment furnace to enhance the crystallinity of the coating crystals and promote uniform distribution of elements.

[0054] The prepared coating was characterized by electron backscatter diffraction technology to analyze the average grain size and the proportion of twin boundaries. The hardness of the sample was tested using a Vickers microhardness tester with a test load of 49.8N and a holding time of 10s. The sample was then placed in a 1000℃ muffle furnace for 10h, with a heating and cooling rate of 10℃ / min. After oxidation, the sample was cooled with the furnace, taken out and weighed, and the oxidation weight gain of the sample was calculated.

[0055] Figure 2 The grain distribution diagram of the Y, Hf and Fe doped Ni3Al coating prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the twin boundaries account for 12.59% of the total grain boundaries, the average grain size is 4.93μm, the Vickers hardness is 290HV, and the oxidation weight gain is 0.105mg / dm 2 Compared with Comparative Example 1, the twin boundary density of the Y, Hf and Fe doped Ni3Al coating prepared in Example 1 is increased, and the grain size and hardness are reduced, which indicates that the brittleness of the coating is reduced and the plasticity and toughness are improved by the doping of Fe element. In addition, the oxidation weight gain is reduced, which indicates that the oxidation resistance of the coating is improved by the doping of Hf and Y elements.

[0056] Example 2

[0057] An oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer, wherein the element composition of the bonding layer comprises, by atomic percentage, 0.2wt.% Y, 0.8wt.% Hf, 0.3wt.% Fe, 13.11wt.% Al, and 85.59wt.% Ni.

[0058] A method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer specifically comprises the following steps:

[0059] Step 1: pretreating the surface of the high-temperature nickel-based alloy substrate;

[0060] The surface of the high-temperature nickel-based alloy substrate is polished and cleaned in sequence, so that the surface of the high-temperature nickel-based alloy substrate is mirror-like and smooth;

[0061] Step 2: Ion etching is performed on the surface of the pretreated high-temperature nickel-based alloy substrate to remove residual impurities on the surface and eliminate residual stress on the surface; the conditions for ion etching are: current of 120A, argon gas is filled in the vacuum chamber, bias voltage of 500V, gas flow rate of 100sccm, temperature of 300°C, and etching time of 15min;

[0062] Step 3: a Ni3Al coating doped with Y, Hf, and Fe is plated on the surface of the high-temperature nickel-based alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer; the target material used to prepare the bonding layer is a Ni3Al (YHfFe) target material; the parameters of arc ion plating are: current of 120A, argon gas is filled in the vacuum chamber, the gas pressure is 1Pa, the gas flow rate is 200sccm, the temperature is 300°C, and the spraying time is 100min;

[0063] Step 4: The Ni3Al(YHfFe) bonding layer obtained in step 3 is annealed at 900°C for 6 hours in a high-temperature vacuum environment using a high-temperature vacuum heat treatment furnace to enhance the crystallinity of the coating crystals and promote uniform distribution of elements.

[0064] Figure 3 The grain distribution diagram of the Y, Hf and Fe doped Ni3Al coating prepared in Example 2 is shown in FIG. Figure 3 It can be seen that the twin boundaries account for 13.92% of the total grain boundaries, the average grain size is 4.76μm, the Vickers hardness is 283HV, and the oxidation weight gain is 0.076mg / dm 2 Compared with Comparative Example 1, the twin boundary density of the Y, Hf and Fe doped Ni3Al coating prepared in Example 2 is increased, and the grain size and hardness are reduced, which indicates that the brittleness of the coating is reduced and the plasticity and toughness are improved by the doping of Fe element. In addition, the oxidation weight gain is reduced, which indicates that the oxidation resistance of the coating is improved by the doping of Hf and Y elements.

[0065] Example 3

[0066] An oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer, wherein the element composition of the bonding layer comprises, by atomic percentage, 0.8wt.% Y, 0.2wt.% Hf, 0.5wt.% Fe, 13.09wt.% Al, and 85.41wt.% Ni.

[0067] A method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer specifically comprises the following steps:

[0068] Step 1: pretreating the surface of the high-temperature nickel-based alloy substrate;

[0069] The surface of the high-temperature nickel-based alloy substrate is polished and cleaned in sequence, so that the surface of the high-temperature nickel-based alloy substrate is mirror-like and smooth;

[0070] Step 2: ion etching the surface of the pretreated high-temperature nickel-based alloy substrate to remove residual impurities on the surface and eliminate residual stress on the surface; the conditions of ion etching are: current of 110A, argon gas filled in the vacuum chamber, bias voltage of 600V, gas flow rate of 250sccm, temperature of 330°C, and etching time of 30min;

[0071] Step 3: a Ni3Al coating doped with Y, Hf, and Fe is plated on the surface of the high-temperature nickel-based alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer; the target material used to prepare the bonding layer is a Ni3Al (YHfFe) target material; the parameters of arc ion plating are: current of 145A, argon gas is filled in the vacuum chamber, the gas pressure is 1.3Pa, the gas flow rate is 250sccm, the temperature is 380°C, and the spraying time is 400min;

[0072] Step 4: The Ni3Al(YHfFe) bonding layer obtained in step 3 is annealed at 1100°C for 2h in a high-temperature vacuum environment using a high-temperature vacuum heat treatment furnace to enhance the crystallinity of the coating crystals and promote uniform distribution of elements.

[0073] Figure 4 The grain distribution diagram of the Y, Hf and Fe doped Ni3Al coating prepared in Example 3 is shown in FIG. Figure 4 It can be seen that the twin boundaries account for 14.57% of the total grain boundaries, the average grain size is 4.10μm, the Vickers hardness is 274HV, and the oxidation weight gain is 0.071mg / dm 2 Compared with Comparative Example 1, the twin boundary density of the Y, Hf and Fe doped Ni3Al coating prepared in Example 3 is increased, and the grain size and hardness are reduced, which indicates that the brittleness of the coating is reduced and the plasticity and toughness are improved by the doping of Fe element. In addition, the oxidation weight gain is reduced, which indicates that the oxidation resistance of the coating is improved by the doping of Hf and Y elements.

[0074] Example 4

[0075] An oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer, wherein the element composition of the bonding layer comprises, by atomic percentage, 0.5wt.% Y, 0.5wt.% Hf, 1wt.% Fe, 13.02wt.% Al, and 84.98wt.% Ni.

[0076] A method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer specifically comprises the following steps:

[0077] Step 1: pretreating the surface of the high-temperature nickel-based alloy substrate;

[0078] The surface of the high-temperature nickel-based alloy substrate is polished and cleaned in sequence, so that the surface of the high-temperature nickel-based alloy substrate is mirror-like and smooth;

[0079] Step 2: Ion etching is performed on the surface of the pretreated high-temperature nickel-based alloy substrate to remove residual impurities on the surface and eliminate residual stress on the surface; the conditions for ion etching are: current of 90A, argon gas is filled in the vacuum chamber, bias voltage is 450V, gas flow rate is 220sccm, temperature is 360°C, and etching time is 25min;

[0080] Step 3: After ion etching, a Ni3Al coating doped with Y, Hf, and Fe is plated on the surface of the high-temperature nickel-based alloy substrate to obtain a Ni3Al (YHfFe) bonding layer; the target material used to prepare the bonding layer is a Ni3Al (YHfFe) target material; the parameters of arc ion plating are: current of 150A, argon gas is filled in the vacuum chamber, the gas pressure is 1.6Pa, the gas flow rate is 100sccm, the temperature is 400°C, and the spraying time is 330min;

[0081] Step 4: The Ni3Al(YHfFe) bonding layer obtained in step 3 is annealed at 970°C for 5 hours in a high-temperature vacuum environment using a high-temperature vacuum heat treatment furnace to enhance the crystallinity of the coating crystals and promote uniform distribution of elements.

[0082] Figure 5 The grain distribution diagram of the Y, Hf and Fe doped Ni3Al coating prepared in Example 4 is shown in FIG. Figure 5 It can be seen that the twin boundaries account for 14.87% of the total grain boundaries, the average grain size is 3.89 μm, the Vickers hardness is 224 HV, and the oxidation weight gain is 0.068 mg / dm 2 Compared with Comparative Example 1, the twin boundary density of the Y, Hf and Fe doped Ni3Al coating prepared in Example 4 is increased, and the grain size and hardness are reduced, which indicates that the brittleness of the coating is reduced and the plasticity and toughness are improved by the doping of Fe element. In addition, the oxidation weight gain is reduced, which indicates that the oxidation resistance of the coating is improved by the doping of Hf and Y elements.

[0083] Example 5

[0084] An oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer, wherein the element composition of the bonding layer comprises, by atomic percentage, 1wt.% Y, 1wt.% Hf, 2wt.% Fe, 13wt.% Al, and 83wt.% Ni.

[0085] A method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer specifically comprises the following steps:

[0086] Step 1: pretreating the surface of the high-temperature nickel-based alloy substrate;

[0087] The surface of the high-temperature nickel-based alloy substrate is polished and cleaned in sequence, so that the surface of the high-temperature nickel-based alloy substrate is mirror-like and smooth;

[0088] Step 2: ion etching the surface of the pretreated high-temperature nickel-based alloy substrate to remove residual impurities on the surface and eliminate residual stress on the surface; the conditions of ion etching are: current of 80A, argon gas filled in the vacuum chamber, bias voltage of 300V, gas flow rate of 150sccm, temperature of 400°C, and etching time of 10min;

[0089] Step 3: a Ni3Al coating doped with Y, Hf and Fe is plated on the surface of the high-temperature nickel-based alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer; the target material used to prepare the bonding layer is a Ni3Al (YHfFe) target material; the parameters of arc ion plating are: current of 80A, argon gas is filled in the vacuum chamber, the gas pressure is 2Pa, the gas flow rate is 150sccm, the temperature is 360°C, and the spraying time is 290min;

[0090] Step 4: The Ni3Al(YHfFe) bonding layer obtained in step 3 is annealed at 950°C for 6 hours in a high-temperature vacuum environment using a high-temperature vacuum heat treatment furnace to enhance the crystallinity of the coating crystals and promote uniform distribution of elements.

[0091] Figure 6 The grain distribution diagram of the Y, Hf and Fe doped Ni3Al coating prepared in Example 5 is shown in FIG. Figure 6 It can be seen that the twin boundaries account for 15.28% of the total grain boundaries, the average grain size is 3.62μm, the Vickers hardness is 201HV, and the oxidation weight gain is 0.061mg / dm 2 Compared with Comparative Example 1, the twin boundary density of the Y, Hf and Fe doped Ni3Al coating prepared in Example 5 is increased, and the grain size and hardness are reduced, which indicates that the brittleness of the coating is reduced and the plasticity and toughness are improved by the doping of Fe element. In addition, the oxidation weight gain is reduced, which indicates that the oxidation resistance of the coating is improved by the doping of Hf and Y elements.

[0092] Comparative Example 1

[0093] A pure Ni3Al bonding layer without doping elements, wherein the element composition of the bonding layer comprises: 13.3wt.% Al and 86.7wt.% Ni in atomic percentage.

[0094] The process and parameters of this comparative example 1 are the same as those of the embodiment 1, except that in step 3, a Ni3Al target is used to plate a Ni3Al coating on the surface of the high-temperature nickel-based alloy substrate after ion etching.

[0095] Figure 7 The grain distribution diagram of the pure Ni3Al coating prepared in Comparative Example 1 is shown in FIG. Figure 7 It can be seen that the twin boundaries account for 9.44% of the total grain boundaries, the average grain size is 10.05μm, the Vickers hardness is 302HV, and the oxidation weight gain is 0.132mg / dm 2 .

Claims

1. An anti-oxidation and anti-interdiffusion high-toughness plastic thermal barrier coating bonding layer, characterized in that: The element composition of the bonding layer includes, by atomic percentage, 0.1-1wt.% Y, 0.1-1wt.% Hf, 0.1-2wt.% Fe, 12-14wt.% Al, and 83-87wt.% Ni.

2. The anti-oxidation and anti-interdiffusion high-toughness plastic thermal barrier coating bonding layer according to claim 1, characterized in that: The element composition of the bonding layer includes, by atomic percentage, 1 wt.% Y, 1 wt.% Hf, 2 wt.% Fe, 13 wt.% Al, and 83 wt.% Ni.

3. A method for preparing an anti-oxidation and anti-interdiffusion high-toughness plastic thermal barrier coating bonding layer, characterized in that: The steps include: Step 1: performing ion etching on the pretreated surface of the high-temperature alloy substrate; Step 2: using a cathode multi-arc ion plating process to plate a Ni3Al coating doped with Y, Hf, and Fe on the surface of the high-temperature alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer; Step 3: Perform annealing heat treatment on the Ni3Al(YHfFe) bonding layer obtained in step 2 in a high temperature vacuum environment.

4. The method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer according to claim 3, characterized in that: In step 1, the high temperature alloy substrate is a nickel-based alloy substrate, and the pretreatment operation is: grinding and polishing and cleaning the surface of the nickel-based alloy substrate in sequence, so that the surface of the nickel-based alloy substrate is mirror-like and smooth.

5. The method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer according to claim 3, characterized in that: The conditions for ion etching in step 1 are: current of 80-120A, argon gas is filled into the vacuum chamber, bias voltage is 300-600V, gas flow rate is 100-250sccm, temperature is 300-400°C, and etching time is 10-30min.

6. The method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer according to claim 3, characterized in that: The target material used to prepare the bonding layer in step 2 is Ni3Al (YHfFe) target material.

7. The method for preparing an oxidation-resistant, anti-interdiffusion, high-toughness, plastic thermal barrier coating bonding layer according to claim 3, characterized in that: The parameters of the arc ion plating in step 2 are: current of 80-150A, argon gas is filled into the vacuum chamber, the gas pressure is 1-2Pa, the gas flow rate is 100-250sccm, the temperature is 300-400°C, and the spraying time is 100-400min.

8. The method for preparing an oxidation-resistant, interdiffusion-resistant, high-toughness, and plastic thermal barrier coating bonding layer according to claim 3, characterized in that: In step 3, the annealing temperature is 900-1100° C. and the time is 2-6 hours.

9. The method for preparing an oxidation-resistant, anti-interdiffusion, high-toughness, plastic thermal barrier coating bonding layer according to claim 3, characterized in that: Step 1: grinding and polishing and cleaning the surface of the nickel-based alloy substrate in sequence, so that the surface of the nickel-based alloy substrate is mirror-like and smooth; then ion etching is performed on the surface of the nickel-based alloy substrate; the conditions of ion etching are: current is 80A, argon gas is filled in the vacuum chamber, bias voltage is 300V, gas flow rate is 150sccm, temperature is 400°C, and etching time is 10min; Step 2: using a cathode multi-arc ion plating process to plate a Ni3Al coating doped with Y, Hf, and Fe on the surface of the nickel-based alloy substrate after ion etching to obtain a Ni3Al (YHfFe) bonding layer; the target material used to prepare the bonding layer is a Ni3Al (YHfFe) target material; the parameters of the arc ion plating are: the current is 80A, the vacuum chamber is filled with argon gas, the gas pressure is 2Pa, the gas flow rate is 150sccm, the temperature is 360°C, and the spraying time is 290min; Step 3: The Ni3Al(YHfFe) bonding layer obtained in step 2 is annealed and heat treated at 950°C for 6 hours in a high temperature vacuum environment.